Historia i pamięć zbiorowa w polityce regionalnej (casus Śląska Opolskiego) - Trzcielińska-Polus, Aleksandra (Przegląd Politologiczny, 2018)
The multicultural and multiethnic character of Śląsk Opolski frequently leads to emotionally heated disputes over such symbols of the past as historical monuments, anniversaries of historical events, cemeteries, signs with topographic names and so on, which is reflected in regional policy. History and collective memory are obviously used by the politicians of Śląsk Opolski (both by political parties and minority organizations) for their current political purposes, in order to achieve certain political interests (such as winning or retaining voters) by means of exerting an influence on the regional community or selected groups and by shaping certain attitudes and behaviors. The author refers to concrete examples of debates held in the region to explain the phenomenon of the politicization of history. She ponders the role of researchers, including political scientists, in preventing the politicization of the past and emphasizes the necessity for their taking a stand in the process of forming regional historical policy.